Are the antagonist muscle fatigued during a prolonged isometric fatiguing elbow flexion at very low forces for young adults? - Wang, Lejun; Song, Xiaoqian; Yang, Hua; Wang, Ce; Shao, Qineng; Tao, Haifeng; Qiao, Minjie; Niu, Wenxin; Liu, Xiaodong (Frontiers in Physiology, 2022)
The aim of this study was to examine whether antagonist muscle may fatigue during a prolonged isometric fatiguing elbow flexion at very low forces. Twelve healthy male subjects sustained an isometric elbow flexion at 10% maximal level until exhaustion while multichannel electromyographic signals (sEMG) were collected from biceps brachii (BB) and triceps brachii (TB). Muscle fiber conduction velocity (CV) and fractal dimension (FD) of both BB and TB muscle were calculated to reflect peripheral and central fatigue respectively. CV and FD of TB as well as FD of BB decreased progressively during the sustained fatiguing contraction, while the CV of BB declined at the beginning of the contraction and then increased progressively until the end of the contraction. The result may indicate that during the sustained low-force isometric fatiguing contraction, antagonist muscle may be peripherally fatigued and changes of coactivation activities were modulated not only by central neuronal mechanisms of common drive, peripheral metabolic factors may also take effect.